2021
DOI: 10.1371/journal.pone.0246087
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory biomarkers of COVID-19 disease severity and outcome: Findings from a developing country

Abstract: Aim To identify laboratory biomarkers that predict disease severity and outcome among COVID-19 patients admitted to the Millennium COVID-19 Care Center in Ethiopia. Methods A retrospective cohort study was conducted among 429 COVID-19 patients who were on follow up from July to October 2020. Data was described using frequency tables. Robust Poisson regression model was used to identify predictors of COVID-19 severity where adjusted relative risk (ARR), P-value and 95 CI for ARR were used to test significance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
51
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 27 publications
11
51
1
1
Order By: Relevance
“…The various other parameters were, however, almost similar in both groups. This is in conjunction with most other studies, thus signifying the role of these laboratory parameters in determining the severity of COVID-19 disease and the high rates of mortality [8,13,[17][18]. C-reactive protein and serum ferritin were elevated among non-survivors thus stressing the role of the inflammatory cytokine storm in the disease severity and poor prognosis [13].…”
Section: Discussionsupporting
confidence: 67%
“…The various other parameters were, however, almost similar in both groups. This is in conjunction with most other studies, thus signifying the role of these laboratory parameters in determining the severity of COVID-19 disease and the high rates of mortality [8,13,[17][18]. C-reactive protein and serum ferritin were elevated among non-survivors thus stressing the role of the inflammatory cytokine storm in the disease severity and poor prognosis [13].…”
Section: Discussionsupporting
confidence: 67%
“…Several previous studies have reported that hypokalemia was not associated with the risk of transfer to intensive care and death, as in our study 16,17 . Contrary to these results, hypokalemia was associated with disease severity in 429 patients, and hypokalemia was associated with disease severity and the need for mechanical ventilation in 306 patients 15,22 . According to these studies, this relationship may be due to negative effects such as hypokalemia-induced myocardial dysfunction, ventricular arrhythmia, and respiratory muscle dysfunction 15 .…”
Section: Discussioncontrasting
confidence: 66%
“…Comorbidities were reviewed from the clinical records and dummy encoded (0/1) for each of the five following items: 1. history of arterial hypertension or current anti-hypertensive medication, 2. history of diabetes or current antidiabetic medication, 3. prior cardiovascular event (myocardial infarction or revascularization procedure, stroke or transient ischemic attack, or diagnosis of peripheral arterial disease), 4. history of hyperlipidemia or lipid-lowering agents in current medication, 5. active smoking habit. Further, commonly reported laboratory values for high-risk COVID-19 were noted from the clinical records (creatinine, C-reactive protein, leucocyte as well as thrombocyte counts, relative lymphocyte count, d-dimer, and lactate dehydrogenase levels) [16][17][18][19]. Laboratory tests were performed on the day of the CT scan (+/-1 day).…”
Section: Clinical Follow-up Comorbidity and Laboratory Testsmentioning
confidence: 99%